PENGGUNAAN METODE DIRECT INSTRUCTION PELAJARAN AGAMA ISLAM DALAM MENINGKATKAN KEMAMPUAN BERSOSIALISASI DI SLB CG YPPCG BINA SEJAHTERA MANDIRI - Muhammad Shubki; Mukhlis Fatkhurrohman; Iffah Mukhlisah (Institut Islam Mamba'ul 'Ulum Surakarta, 2021)
This study aims to determine the use of direct instruction method. This research is a qualitativeresearch. The subject of the study was SLB CG-YPPCG Bina Sejahtera Surakarta. In this study using data collection methods through observation, interviews, and documentation. Meanwhile, data analysis uses data reduction, data presentation, and data verification. The results show that the characteristics of students at SLB CG-YPPCG Bina Sejahtera Surakarta are experiencing slowness in doing something or difficulty in understanding and learning new things. Then the direct instruction method used in learning is that the teacher provides learning with a simple and sequential arrangement of steps. So with this model direct instruction learning can improve social skills for mentally retarded children at SLB CG-YPPCG Bina Sejahtera Surakarta.